Development of a nanobody tagged with streptavidin-binding peptide and its application in a Luminex fluoroimmunoassay for alpha fetal protein in serum. Issue 40 (22nd June 2020) - Chen, Qi; Sun, Danyang; Pei, Hua; Su, Benchao; Bao, Kunlu; Cao, Hongmei; Zhang, Chenghui; Hammock, Bruce D.; Liu, Xing
Abstract : A nanobody/streptavidin-binding peptide fusion protein was developed and proved to be a very promising immunological diagnosis reagent for disease-related biomarkers. Abstract : Sensitive and accurate detection of disease-related biomarkers can promote the early screening and diagnosis of cancers for improving the prognosis and survival of patients. Herein alpha fetal protein (AFP) was selected as the model macromolecule antigen and we developed AFP-specific alpaca nanobodies (Nbs) from an immunized phage-displayed Nb library. Then Nbs tagged with streptavidin-binding peptide (Nb-SBP) were constructed and used to develop an Nb-SBP-mediated fluoroimmunoassay based on the Luminex-200 system (NS-LFIA). Based on the optimal experimental conditions, the NS-LFIA has a limit of detection of 0.237 ng mL −1 with a linear detection range of 0.49–125 ng mL −1 . The average recovery rate and relative standard derivation were in the range of 98.2–110% and 2.8–13.8%, respectively. The NS-LFIA is highly selective for AFP and ignorable cross-reaction was observed with the other biomarkers. The content of AFP in clinical serum samples was determined by both the developed NS-LFIA and the Roche E601 automatic chemiluminescence immunoassay analyzer and a good correlation was obtained between the two methods ( R 2 = 0.9894). Moreover, the Nb-SBP can significantly improve the homogeneity of the fluorescent signals tested by the Luminex-200 system compared with the biotinylated conventional monoclonal antibodies, which could reduce the magnetic microsphere consumption and test cost by decreasing the repetitions of each sample. Thus the results demonstrated that the Nb-SBP was a very promising immunological diagnostic reagent and indicated the applicability and reliability of the NS-LFIA for sensitive detection of AFP and other disease-related biomarkers.